Challenges and experiences faced by Malaysian undergraduates in coping with low academic motivation during the COVID-19 pandemic - Ang, Brenda Shau Ying; Samiya Mir,; Lai, Ge Xin; Wong, Nicholas Yi Zheng; Wong, Jia Jia (Penerbit Universiti Kebangsaan Malaysia, 2021)
COVID-19 pandemic has impacted educational institutions worldwide due to a sudden transition of the learning system, which has affected students' academic performances in several aspects. This qualitative study examines Malaysian undergraduates' challenges and experiences in coping with low academic motivation during the COVID-19 pandemic with this qualitative study. One to one semi-structured interviews were conducted among a total of 24 undergraduates in Malaysia between the age of 19 to 24 through online platforms. The data collected was analysed by interpretative phenomenological analysis (IPA). Four analytic themes are presented: (1) intrinsic challenges; (2) extrinsic challenges; (3) intrinsic motivation, and (4) extrinsic motivation. Future research is suggested to take cultural differences, quality of mental health and student’s perception of stress into consideration.